2000
DOI: 10.1590/s0037-86822000000100015
|View full text |Cite
|
Sign up to set email alerts
|

Considerações sobre pulgas (Siphonaptera) da raposa Cerdocyon thous (Canidae) da área endêmica de leishmaniose visceral de Jacobina, Bahia, Brasil

Abstract: No período de julho a setembro de 1998 foram coletadas 152 pulgas em 18 exemplares da raposa Cerdocyon thous capturados na área endêmica de leishmaniose visceral de Jacobina, Estado da Bahia. As pulgas foram identificadas como: 136 Rhopalopsyllus lutzi lutzi, 11 Pulex irritans, 2 Ctenocephalides canis, 1 Ctenocephalides felis felis e 2 Xenopsylla cheopis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
13
1
1
Order By: Relevance
“…The variety of natural environments and climates occurring in this country is impressive and favours the establishment of different parasites in all geographical regions. In the same way, dogs and cats living in either urban or rural areas may eventually live in close contact with livestock and wildlife species (e.g., foxes, wild cats, and opossums), which ultimately may favour the exchange of ectoparasites such as fleas and ticks with these animals [320-323]. For instance, R. sanguineus s.l.…”
Section: Reviewmentioning
confidence: 99%
“…The variety of natural environments and climates occurring in this country is impressive and favours the establishment of different parasites in all geographical regions. In the same way, dogs and cats living in either urban or rural areas may eventually live in close contact with livestock and wildlife species (e.g., foxes, wild cats, and opossums), which ultimately may favour the exchange of ectoparasites such as fleas and ticks with these animals [320-323]. For instance, R. sanguineus s.l.…”
Section: Reviewmentioning
confidence: 99%
“…In Spain, results of a survey of fleas in carnivorous mammals showed that only P. irritans was found on red foxes ( V. vulpes ). During a leishmaniosis study in the Brazilian State of Bahia, crab-eating foxes ( Cerdocyon thous ) were studied [14]. All 18 specimen tested were infested with fleas.…”
Section: Reviewmentioning
confidence: 99%
“…which are respectively the etiological agents for Bubonic Plague, Murine Typhus and Bartonellosis, which are zoonotic diseases of rodents (Ribeiro et al, 2003;Billeter et al, 2011). It must also be considered that Xenopsylla cheopis, which is adapted to the urban environment and to men, can parasite not only rodents but also other animal species, with its parasitism already described in foxes (Cerdocyon thous) (LINNAEUS, 1789) (Cerqueira et al, 2000;Ribeiro et al, 2003).…”
Section: Discussionmentioning
confidence: 99%